Injeção subaracnóidea inadvertida de corticoíde em tratamento de dor crônica da coluna lombar. Relato de caso - D'Angelo Vanni, Simone Maria [UNESP] (Elsevier, 2004)
BACKGROUND AND OBJECTIVES: Before epídural steroids were used in chronic lumbar pain, subarachnoid injection of these agents was the treatment of choice. Although still preconized by some authors, this technique may lead to severe complications with neurological sequelae. This report aimed at describing a case of accidental subarachnoid injection of steroid associated to local anesthetics during epidural puncture to treat lumbar pain. CASE REPORT: Male patient, 46 years old, followed byneuro-surgery for presenting right sciatic pain for 9 month, refractory to clinical treatment due to L 4-L 5 disk protrusion confirmed by CT scan, without neurological deficit. Epidural puncture for pain treatment was performed in L 4-L 5 with 17G needle and 10 mL solution were injected containing 4 mL of 0.25% bupivacaine, 80 mg methylprednisolone and 4 mL of 0.9% saline. Although there has not been CSF reflux, 5 minutes after injection there were sensory block in T 4 and motor block in T 6, associated to blood pressure and heart rate decrease. CONCLUSIONS: Accidental subarachnoid injections with the association of steroids for pain relief may cause adverse effects. There are several risks, varying from mild transient symptoms to nervous injuries, including spinal cord injuries. Our patient had no sequelae from the accidental subarachnoid injection, probably because it has been a single injection.
Accidental subarachnoid steroid injection during chronic lumbar pain treatment. Case report
Keywords: Complications: accidental injection; Drugs, Steroids; Pain, Chronic; antiinflammatory agent; bupivacaine; ephedrine; lidocaine; local anesthetic agent; methylprednisolone; nonsteroid antiinflammatory agent; sodium chloride; steroid; tricyclic antidepressant agent; adult; bradycardia; case report; chronic pain; computer assisted tomography; drug administration route; epidural anesthesia; human; hypotension; injection; intervertebral disk hernia; ischialgia; low back pain; lumbar spine; male; nerve injury; neurologic disease; pain assessment; puncture; sensory dysfunction; spinal cord injury; symptom; technique; visual analog scale